Summer hours = L' heure d'été - Assayas, Olivier 1955-; Gautier, Éric 1961-; Binoche, Juliette 1964-; Berling, Charles 1958-; Renier, Jérémie 1981- (<<The>> Criterion coll., 2010)
The divergent paths of three adult siblings collide when their mother, heiress to an exceptional 19th century art collection, dies suddenly.
Aspect ratio 1.85:1, 16:9 widescreen. - New high-definition digital transfer, supervised by director Olivier Assayas and approved by Assayas and cinematographer Eric Gautier
Orig.: Frankreich 2008
Enth. new video interview with Assayas ; making-of documentary featuring interviews with Assayas and actors Charles Berling and Juliette Binoche, and showing the cast and crew on set ; 'Inventory', an hour-long documentary by Olivier Geoinard, shot partly in Paris's Musée d'Orsay, that examines the film's approach to are ; a booklet featuring an essay by critic Kent Jones